Comparing Community Meeting Attendance and Efficacy in Two Specialist Medium Secure Inpatient Wards at St Andrew’s Hospital - Aditya Bose-Mandal; Antrita Patel; Sadra Ghazanfaripour; Donna Arya (BJPsych Open, 2025)
Aims: Community meetings in inpatient psychiatric settings provide a structured opportunity for patients and staff to discuss ward updates, raise concerns, and plan for the upcoming week. These meetings, often chaired by patients, are integral to promoting engagement and empowerment.